APLIKASI EDUKASI PENCEGAHAN PENYAKIT PROSTAT BERBASIS ANDROID (STUDI KASUS RS ISLAM ARAFAH KOTA JAMBI) - Kahar, Novhirtamely; Suana, Irma; Pahlevi, M. Roza (LP2M Universitas Nurdin Hamzah, 2023)
Prostate disease is one of the significant health problems for men, but awareness of the importance of prevention and treatment of this disease is still relatively low. Therefore, the purpose of this research is to build an Android-based educational application specifically focused on the prevention of prostate disease. This research was conducted at Arafat Jambi Islamic Hospital, and this application will be a relevant case study in an effort to increase public awareness about the importance of maintaining prostate health. The input in this research involves the use of the Flutter framework and the Dart programming language as the main tools in building educational applications. The output of this research is an Android application that can be downloaded and used by the community at large. The app will provide reliable information on prostate disease prevention, including steps that can be taken to keep the prostate healthy. The app will also provide advice on a healthy diet, and an active lifestyle. The expected outcome of this research is an increase in the knowledge and awareness of the public, especially men, about prostate disease prevention. Thus, it is hoped that the number of cases of prostate disease that are detected late can be reduced, improving the quality of life of men, and reducing the negative impact of this disease on society.